Effect of electroporation on radiosensitization with cisplatin in two cell lines with different chemo- and radiosensitivity - Kranjc, Simona (Radiology and oncology (Ljubljana), 2003)
Aim. Radiosensitization with cisplatin can be enhanced by electroporation of cells and tumours. The aim of this study was to extend our previous studies ontwo carcinoma tumour models with different chemo-and radiosensitivity in order to evaluate whether this treatment is effective also on less chemo-and radiosensitive tumour cells. Materials and methods. This in vitro study was performed on carcinoma SCK and EAT-E cells. The cytotoxicity of three-modalitytreatment consisting of cisplatin, electroporation and irradiation was determined by the clonogenic assay. Results. The radiosensitizing effect of cisplatin on the two cell lines was greatly enhanced by electroporation. By this combined treatment, less chemo and radiosensitive EAT-E cells were rendered as sensitive as more chemo and radiosensitive SCK cells. Conclusion. The enhancement of cisplatin-induced radiosensitization of cells by electroporation could be beneficially used in the treatment of intrinsically less chemo- and radiosensitive tumours.
Keywords: Celica, preživetje; Cell Survival; Cisplatin; Drug Delivery Systems; Drug Effects; Electroporation; Elektroporacija; Radiation Effects; Radiation Tolerance; rak (medicina); Sevanje, toleranca; therapy; Tumor Cells, Cultured; tumorske celice; Tumorske celične kulture; Zdravilo, sproščanje, sistemi; zdravljenje